Educational Farms in Poland from the Perspective of Visual Sociology - Marcysiak, Tomasz (Eastern European Countryside, 2025)
This article explores the use of visual materials (photographs) as tools for social understanding and methods for collecting and interpreting visual data in the sociology of rural areas. The photographs presented were taken during a nearly two-year research project titled ’Educational Farm – An Innovative Form of Entrepreneurship in Rural Areas,’ aimed at diagnosing the resources of Polish rural areas that could serve as a sustainable foundation for the development of educational farms in collaboration with educational institutions (preschools, primary and secondary schools). The photographic documentation not only reveals the specifics of education on farms but also provides a basis for discussing the future of the Polish education system, particularly in the context of educational trends such as adventure pedagogy and alternative learning methods beyond traditional school settings (outdoor learning, outdoor education).